Blended Learning sebagai solusi Pembelajaran di Era New Normal - Ahmad Mujahid (IAI DDI POLEWALI MANDAR, 2022)
Abstract This research is a qualitative descriptive study conducted at STAI DDI SIDRAP on PAI study program students for the 2021/2022 academic year which aims to increase the learning abilities and interest of PAI study program students at STAI DDI Sidrap. The results show that the blended learning model can encourage participants to use online communication in developing knowledge so that learning is very effective, efficient to improve students' abilities to be fun, students' interest in learning is greater with a comfortable learning environment. Keywords: Blended Learning, New Normal